Capsule endoscopy in a network cooperation: assessment of the experience in 822 patients. (September 2013) - Farnbacher, Michael Julius; Keles, Murat; Meier, Michael; Hagel, Alexander; Schneider, Thomas
Abstract: Introduction. Capsule endoscopy (CE) is firmly established as a standard procedure in the diagnostic algorithm of occult or obscure gastrointestinal bleeding and Crohn's disease. Despite its excellent diagnostic yield, missing expertise, reading time and financial expenditure limit an area-wide availability. A multicentric cooperation might compensate these disadvantages. Methods. CE device was bought by a central hospital (CH). Requested equipment is transported to the network partner (NP) and the procedure performed at the spot in personal responsibility. Video reading is exclusively done in the CH. Results. Within 10 years, 822 CE (438 m., 384 f.; 63 ± 17 (13–92) years) were performed by 18 cooperating gastroenterological departments. 587/822 (71%) CE were done at NP, 235/822 (29%) in the CH. Between 2002 ( n = 39) and 2011 ( n = 123) the annual number of CE increased threefold. 95% of the capital investment in each cooperating hospital could be avoided by sharing one workstation within the network. Leading indication for CE was suspected mid-GI-bleeding (80%). Mean latencies between requested date and actual examination were 0 and between equipment's return and report 2 days. 45/191(24%) flexible enteroscopies performed in the CH followed CE findings from NP. Discussion: Our 10 years experience show that mobile use of CE is feasible providing quality parameters similar to a single center solution, increases the number of CE investigations, therefore, improves reading expertise and enables both an area-wide and economic offer for this technique. Additionally, patients with the need for invasive enteroscopy are identified and attracted to that NP who provides an invasive SB endocopy device.